Utilizing journey mapping to evaluate youth programs and social service systems: Case studies - Emma Connell; Amanda Petersen; Mongkol Teng (The Evaluation Center at Western Michigan University, 2023)
Background: Journey mapping is a relatively new, promising method for use in the evaluation sector. In this method, individuals who have gone through a program or system provide feedback on the process in a chronological way, highlighting successes and challenges they have encountered through the process. This article provides an overview of the method and three case studies describing how journey mapping has been used to evaluate youth programs and social service systems. Purpose: To aid evaluators in understanding journey mapping and the ways in which it can be applied to various evaluation projects with the intention to help them determine whether or not the method is appropriate in their practice. Setting: Journey mapping can be applied in evaluations examining how individuals and groups interact with programs, organizations, and systems. Data collection and analysis: The journey mapping method, including data collection through focus groups and interviews and thematic analysis of notes and transcripts. Findings: Journey mapping is a method that can illuminate successes and challenges individuals and families face when interacting with a program, organization, or system. Specific recommendations for study design, data collection, analysis, and reporting are offered for evaluators' consideration.